Respuesta :

kdu700

Answer:

[tex]x = -1[/tex], [tex]y = 4[/tex]

Step-by-step explanation:

[tex]2x + 3y = 10[/tex]

[tex]3x + 5y = 17[/tex]

By using substitution:

[tex]2x + 3y = 10[/tex]

[tex]2x = -3y + 10[/tex]

[tex]x = -\frac{3}{2} y + 5[/tex]

[tex]3x + 5y = 17[/tex]

[tex]3 (-\frac{3}{2}y + 5) + 5y = 17[/tex]

[tex]\frac{1}{2} y + 15 = 17[/tex]

[tex]\frac{1}{2} y = 2[/tex]

[tex]y = 4[/tex]

[tex]x = -\frac{3}{2}y + 5[/tex]

[tex]x = -\frac{3}{2} (4) + 5[/tex]

[tex]x = -1[/tex]

2x=10-3y; x=(10-3y)/2;
plug in the value of x into the second equation:
3((10-3y)/2)+5y=17 then solve for y:
(30-9y)/2+5y=17
(30-9y)2+10y/2=17
(30+y)2=17
30+y=17/2
y=8.5-30
y=-21.5 plug the value of y into the previous equation and solve for x
x=(10-3y)/2
x=(10-3(-21.5))/2
x=74.5/2
x=37.25
ACCESS MORE